Effects of Dietary Fatty Acids on Bovine Oocyte Competence and Granulosa Cells - Sharma, Arpna; Baddela, Vijay Simha; Roettgen, Volker; Vernunft, Andreas; Viergutz, Torsten; Dannenberger, Dirk; Hammon, Harald M.; Schoen, Jennifer; Vanselow, Jens (Frontiers in Endocrinology, 2020)
Here we assessed the effects of dietary essential fatty acids on the developmental competence of oocytes in cows and on the functionality of follicular granulosa cells (GC). Lactating German Holstein cows were supplemented from week 9 ante partum (ap) until week 8 post-partum (pp) in four dietary groups designed as (i) control (CTRL: coconut oil), (ii) essential fatty acid (EFA: linseed and safflower oil), (iii) conjugated linoleic acid (CLA: Lutalin®), and (iv) EFA+CLA (mixture of linseed oil, safflower oil and Lutalin®). EFA, CLA or EFA+CLA supplementation did not improve in vitro embryo production. However, higher proportions of α-linolenic acid (ALA) and cis-9, trans-11 CLA were observed in the follicular fluid suggesting the exposure of GC to relatively high levels of ALA and cis-9, trans-11 CLA. Consequently, we tested different concentrations of ALA and cis-9, trans-11 CLA in a bovine GC culture model for their effects on steroid production, marker gene expression and viability. Both fatty acids upregulated CD36 and downregulated the expression of FOXL2, while ALA significantly increased SOX 9 transcript levels. Both ALA and cis-9, trans-11 CLA reduced the CCND2 expression and cis-9, trans-11 CLA induced apoptosis. ALA and cis-9, trans-11 CLA significantly down-regulated the expression of STAR, CYP19A1, FSHR, LHCGR and decreased the 17β-Estradiol (E2) and progesterone (P4) production. In conclusion, dietary lipids did not improve in vitro embryo production, while ALA and cis-9, trans-11 CLA affected the morphology and functionality of GC. This could suggestively lead to compromised follicle development and ovarian cyclicity in dairy cows.